Transformation of a Modern Newsroom Workforce: A case study of NYC journalist network histories from 2011 to 2015. (21st April 2019) - Kosterich, Allie; Weber, Matthew S.
Abstract : Digital transformation continues to impact the news industry and news organizations are adapting accordingly through shifts in required skills and prescribed job positions of journalists. In order to examine the changing nature of the modern journalist, a case study was conducted examining the employment histories of New York City journalists ( n = 3587). Social network analysis was used to better understand the career trajectories of journalists within the dataset, with a specific focus on understanding the development of new jobs for journalists in data, analytic, social, and mobile-oriented job positions. Findings demonstrate important differences between traditional employment patterns and those of employees in jobs requiring new skills and knowledge of new technology.